Navigating the decision landscape: understanding interstitial cystitis/bladder pain syndrome patients’ motivations and medical support needs for fecal microbiota transplantation: a qualitative research - Hongyuan Liu; Yaodi Wei; Peng Jiang; Siyu Fan; Yu Zhao; Zhi Li; Shiyu Wang; Na Zhang; Junjie Zhi; Qun Wei; Yifeng Gu; Bihong Yang; et al. (BMC Complementary Medicine and Therapies)
Abstract Background Interstitial cystitis/bladder pain syndrome (IC/BPS) patients often confront limited treatment options, leading them to contemplate fecal microbiota transplantation (FMT) as an alternative therapy. Recognizing the factors influencing their decision-making process and their medical support needs is imperative. This study aimed to investigate the determinants of decision-making and the medical support requirements of IC/BPS patients considering FMT as an alternative treatment. Methods Semi-structured interviews were conducted with 18 IC patients to explore their motivations for choosing FMT and their decision-making prerequisites. Data analysis was conducted using a thematic approach. Results Two overarching themes and seven subthemes were identified. (1) Reasons for choosing FMT. ① Awareness of the complexity and intractability of the disease: Patients exhibited a profound understanding of IC’s intricacy and intractability, which ignited their interest in FMT; ② Current treatment dissatisfaction boosted interest in FMT: Discontent with conventional treatments significantly impelled patients to consider FMT; ③ FMT is perceived as a side-effect-free holistic regulatory therapy; ④ Severe negative emotions drive patients to choose FMT: Strong emotions, such as anxiety and desperation, were motivating factors for patients choosing FMT. (2) Professional assistance required when choosing FMT. ① Access to Information Sources: Patients expressed a strong need for comprehensive information resources to aid their decision-making; ② Patients want to learn about peers’ treatment experiences and outcomes: Patients sought insights from individuals who had undergone FMT; ③ Patients want more opportunities for communication with healthcare providers: enhanced communication channels with healthcare professionals were desired. Conclusions These findings emphasize the significance of addressing the intricate informational and emotional needs of IC/BPS patients when considering FMT as a treatment option. Tailored information delivery and peer support can facilitate informed decision-making within the context of FMT for IC/BPS. Trial registration The trial registration number, CHiCTR2100048970, was registered on July 19, 2021.